The principles of muhammadan jurisprudence according to the hanafi, maliki, shafi'i and hanbali schools - Rahim, Sir Abdur ([S.l.] : Forgotten Books, 1990)
University of Calcutta, as Tagore Professor for the year 1907, and I greatly regret that there should have been so much delay, due to reasons altogether personal to myself, in the publication of the book. The first Chapter is intended to be introductory, and its usefulness will, I trust, be apparent, especially with reference to the topics discussed inC hapters XI to XII. I ought to mention that, in writing the earlier portion of the first Chapter, I derived valuable suggestions fromM r. Macdonald sexcellent treatise on Muhammadan Theology. Chapters II to Vcontain an exposition of A l-U sul or theS cience of Law, as developed by theM uhammadan jurists between the eighth and the fourteenth centuries of the Christian Era. Much of this part of the book is practically a translation of Sadru sh-S hari ats Taudih which was written sometime in the fourteenth century and is recognized as a standard work on the subject. The other writings on Usul which I have largely consulted areT aftdzdnis Talwih ,which is a commentary on 1T audih ,F akhru l-I sldm sA l-U sul and its commentary Kashfn 1-I srar ,M usullumu th-T habut ,by Muhibbullah and its commentaries by Bahrul Ulum and others, A ttaqrir-wa tT ahbir ,by I bn Hammam, Nuru l-A nwar ,by Mullah Jiwan ;J am ulJ aw mi ,by Tajuddin Subki with its commentary by A l-M halli and the gloss known as A l-A yatu l-B ayyin tand A l-M ukhtasar by I bn Hajib with Qdi Udud scommentary thereon. In writing the remaining chapters I have not had the same invaluable help of these eminent jurists, who did not think fit to pursue their investigations beyond the limits of the topics dealt with inC hapters II to V. (Typographical errors above are due to OCR software and don't occur in the book.) About the Publisher Forgotten Books is a publisher of historical writings, such as: Philosophy, Classics, Science, Religion, History, Folklore and Mythology. Forgotten Boo.